Partisan Politics and the Road to Plutocracy - Blair Fix (Economics from the Top Down, 2025)
As billionaires dance in the halls of the second Trump administration, it's haunting how well Plutarch's two-thousand-year-old words describe the state of American politics. It's a barren landscape of plutocratic insatiability. *** How did it get this way? *** One way to tell the story is to look at the battle between the ruling class and everyone else — a battle which elites are obviously winning. But another way to understand the struggle is to look at the war between factions of the ruling class — a battle that plays out largely within partisan politics. *** On this partisan front, the historical backdrop is that for forty years, Republicans have been playing a political shell game. As Jay Michaelson puts it, Republicans “appear populist … but act plutocrat”. What's disorienting is that this shell game has worked. Although Republicans have historically governed for the benefit of the rich, they have recently rebranded themselves (successfully, it seems) as the party of the working class. *** Is this new Republican messaging sincere? Or is it gaslighting? Well, Trump's billionaire-stacked administration is quickly answering the question for us. However, this essay is not primarily about Trump, nor is it focused on the future. Instead, it's a journey into how the partisan politics of the past have shaped the American plutocracy of today. *** The essay consists of a deep dive into the realm of US state politics. The story will be simple and repetitive. Across states, I will measure the degree to which Republicans control each state's legislature. Then I will observe, in a statistical sense, the policies and social outcomes that follow. That's it. Of course, I'll add commentary along the way. But the goal is to let the evidence speak for itself. And what leaps from the data is this: Republican control of state legislatures is systematically associated with the rich being (and becoming) richer. In short, American plutocracy seems to be a quintessentially Republican affair. *** And that's not all. *** As we journey into the depths of US state politics, the plot will thicken. We'll find striking partisan differences in the language used in state bills. We'll see the many ways that Republicans help the rich and hurt workers. We'll see the impact partisan politics have on the population as they work longer hours with less security. We'll see the toll that Republican control takes on human welfare. And we'll study the ways that Republicans gain power, despite enacting policies that are self-evidently bad for the majority. And we'll reflect on the reasons that plutocracy can become self-reinforcing. *** Think of the evidence that follows as a case study in how the machinery of democracy can be used to benefit the few and harm the many. It's a warning from the past about tactics that will no doubt be intensified by Trump and his posse of plutocrats.
Keywords: P1; P12; P14; D72; D6; D3; I1; H2; J5; 330; capital as power; bankruptcy; crime; Democratic Party; differential accumulation; distribution; dominant capital; health; inequality; mortality; political parties; Republican Party; sabotage; states; tax; Trump; unions